1985
DOI: 10.1073/pnas.82.23.7919
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping of adeno-associated virus capsid proteins B and C: a possible ACG initiation codon.

Abstract: The three major capsid proteins of adeno-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 23 publications
1
93
1
1
Order By: Relevance
“…Initiation of eukaryotic translation on codons differing at a single position from AUG is inefficient and rare (25). The nucleotides surrounding the AUU codon in antizyme inhibitor uCC comply with the standard context for efficient initiation (15) although not to the same extent as those flanking some previously identified non-AUG-initiating codons (26).…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of eukaryotic translation on codons differing at a single position from AUG is inefficient and rare (25). The nucleotides surrounding the AUU codon in antizyme inhibitor uCC comply with the standard context for efficient initiation (15) although not to the same extent as those flanking some previously identified non-AUG-initiating codons (26).…”
Section: Discussionmentioning
confidence: 99%
“…The seeming paradox is apparently resolved in two ways. VP-2 has been reported to initiate translation at an ACG upstream from the first potential AUG (Becerra et al, 1985). VP-1 translation may require a second splice of the p40 transcript, either in addition to or in place of that shown in Fig.…”
Section: Proteinsmentioning
confidence: 99%
“…BECERRA et al (2) speculate that use of non-AUG as initiation codon for translation of the AAV-B protein could regulate the relative synthesis of proteins B and C in vivo if these proteins are translated from the same mRNA. Assuming the initiation signal for AAV-B protein (initiation codon ACG) is weak compared to the signal for AAV-C protein (initiation codon AUG), then it would be possible for the cell to obtain a fixed ratio of B protein/C protein.…”
Section: Resultsmentioning
confidence: 99%
“…BECERRA et at. (2) have shown that the methionyl-tRNA dependent initiation ofadeno-associated virus (AAV) B protein starts from an ACG codon, and ANDERSON et al (1) have shown that an ACG codon (replacing the AUG used in vivo to initiate the synthesis of Abbreviations: ADHI (PR) = alcohol dehydrogenase I (promoter); bp = base pair(s).…”
Section: Introductionmentioning
confidence: 99%